Les clins d’oeil du pasticheur: innovation et intertextualité dans Les Atomiques d’Eric Laurrent - Zentai Horváth, Krisztina (Verbum – Analecta Neolatina, 2001)
Is it still possible to renew the novelisitc form? One of the young authors published by Minuit, Eric Laurrent shows that such an enterprise is not as hopeless as it might seem. Laurrent sets his novel in the genre ot the spy novel and hence establishes a communication with the reader deceiving all his expectations. On the one hand, this exaggerated intertextual fullness shows the narrative as an artificial product so as to keep the reader at a certain distance from the fiction. On the other hand, using a series of discours transcending our everyday life, the novel gathers the scattered fragments of the contemporary world. Doing this, it obeys a postmodern aesthetics which, unlike the modernity, doesn’t try to provide an answer to the chaos but integrates it.